Carbon Offsets with Endogenous Environmental Policy - Strand, Jon (2012)
Interests in obtaining carbon offsets in host countries for CDM projects may serve as an obstacle to implementing more stringent general environmental policies in the same countries. A relatively lax environmental policy, whereby carbon emissions remain high, can be advantageous for such countries as it leaves them with a higher than otherwise scope for future emissions reductions through CDM and other offset projects. In this paper, the potential to affect the availability of future CDM projects is shown to distort environmental and energy policies of CDM host countries, in two ways. First, policies to reduce the use of fossil energy are weakened. This in turn weakens private sector incentives to switch to lower-carbon technology through CDM projects. CDM host governments then also find it attractive to subsidize this switch, in order to maximize the country's advantage from the CDM.